SINAA.CO: the future sustainable disposable blood pressure cuff cover - Ahmad, Azmir; Ismail, Mohamad Wafiuddin; Hamzah, Nazirah; Jamaludin, Inas Zuhairah; Nik Kamrulzaman, Nik Adlin Syazana; Mohd Saad, Saidatie Nadwa; Mohd Sanusi, Nur Sabila; Mualimin, Arnihidayah (2022)
Sphygmomanometer is a medical instrument that widely used by nurses to measure blood pressure (BP) of patients in hospitals and on-field medical procedures. Since BP cuff is applied directly on patient’s skin, hygienic practice is important to prevent person-to-person bacterial infection. Problem statement: A study reported that BP cuff was among the medical instrument that highly contaminated with pathogenic bacteria. The percentage of contamination on BP cuff was high in almost departments of the hospitals especially in critical areas, such as intensive care unit wards and emergency department. This indicates the inefficient of current practice in cleaning the BP cuff procedure. Thus, it is crucial to improve the hygienic practice among the nurses on the use of sphygmomanometer by proposing an innovation that assisting the nurses in improving their works. Objective: To reduce the contamination of bacteria on BP cuff by innovating a BP cuff cover, named as SINAA.CO, that can improve the hygienic practice among the nurses. Method: The SINAA.CO will be made by oxo-biodegradable plastic with rectangle shape to fit the shape of BP cuff. One edge of SINAA.CO will be folded and sealed to serve as inserts for the BP cuff. Prior to BP measurement, the part of BP cuff that will contact with patient’s skin is layered with SINAA.CO and the edge of BP cuff will be inserted into inserts of SINAA.CO. Once the procedure is done, the SINAA.CO can be simply removed from the BP cuff by taking out the insertion part of SINAA.CO from the BP cuff. Novelty: This BP cuff is the first disposable BP cuff that innovated with simpler design for human use. It is easier to be used by the nurses to encourage their works in measuring BP with hygienic practice and simultaneously reducing the person-to-person bacterial infection. Furthermore, the SINAA.CO is made of environment-friendly material, which is oxo-biodegradable plastic, and the cost is cheaper than the available disposable BP cuff cover in the market. Benefits to society: The use of SINAA.CO can reduce the person-to-person bacterial infection during the BP measurement procedure, which eventually reducing the prevalence of infectious diseases in Malaysia. The design of SINAA.CO that is easy to be used by the nurses will increase the quality of nurses’ works in practicing hygienic procedure. The use of bio-degradable material also will make it as a more sustainable products that can be sustainably manufactured while saving the environment.